Editorial - Brown, Allan; Kerslake, Andrew (Groupwork, 2020)
This is the Editorial to the first issue of Groupwork. We are now putting all back issues on line. Articles have been scanned to pdf files. Though they may not look it, these files are to some degree searchable. This issue was published nearly 30 years ago. We have stated author details as received at time of publication.